The potential to propagate coconut clones through direct shoot organogenesis: A review. - Kong, E. Y.; Biddle, J.; Foale, M.; Panis, B.; Adkins, S. W.
The production of a single stem, which is a characteristic of most members of the Arecaceae family, is a distinctive feature of the coconut palm (Cocos nucifera L.), oil palm (Elaeis guineensis Jacq.)and date palm (Phoenix dactylifera L.). This feature has been a constant for many palm species since the late Cretaceous period, but rare cases of shoot branching in coconut do occur. This original feature leads to multiple stem formation and is considered to be a novel trait. An understanding of the role of plant growth regulators in shoot branching offers a new pathway to produce multiple stem buds in a palm through in vitro culture. As the world's coconut crop is now facing a decline in productivity due to palm aging, extreme climate events, and biotic and abiotic stresses, this approach could help to meet the increasing demand for elite coconut seedlings. Hence, this review examines the potential for direct shoot organogenesis to be used as an option for the clonal propagation of coconut. Cytokinins are essential to induce direct shoot formation. Although more research is needed to confirm the best method to produce coconut clones, based on the literature, for direct shoot organogenesis, it is expected that a treatment of thidiazuron only (for embryo)or in combination with picloram (for immature inflorescence)in Eeuwens Y3 medium would produce the best likelihood of success. The feasibility of this pathway of plantlet production in coconut is bolstered by the relatively easy direct shoot organogenesis now available as an alternative clonal propagation protocol for oil palm and date palm.
Keywords: CLONING; COCONUT; COCOS NUCIFERA; MICROPROPAGATION; ORGANOGENESIS; TISSUE CULTURE